2021
DOI: 10.35870/ijmsit.v1i1.231
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ Work-Life Balance Reviewed From Work From Home Aspect During COVID-19 Pandemic

Abstract: The COVID-19 pandemic suddenly made the company inevitably has to run its operational activities in a way of work from home. The sudden change in the operational activity system can have an impact on the work-life balance of employees. In this study, the researchers wanted to know the work-life balance of the employees during the COVID-19 pandemic in terms of work from home. The research method used is a survey method with descriptive verification research type. The data used are primary data obtained from dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 6 publications
(7 reference statements)
0
26
0
1
Order By: Relevance
“…Indicators used in this study manifest the effect of work discipline on employee performance. Working from home requires good time management, work-life balance, and high commitment (Irawanto et al, 2021;A. Putri & Amran, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Indicators used in this study manifest the effect of work discipline on employee performance. Working from home requires good time management, work-life balance, and high commitment (Irawanto et al, 2021;A. Putri & Amran, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, allowing employees to stipulate their work hours, workdays and days off improves the work-life balance of employees working from home. Therefore, work flexibility may be an important factor in remote work arrangements and behaviours [ 37 ].…”
Section: Contextual and Theoretical Backgroundmentioning
confidence: 99%
“…Previous studies showed that, compared to in-person work arrangements, WFH allows workers to have flexible work schedules, less traveling time, and more support from family members, and thus fosters better balance between work and life (18,(33)(34)(35)(36). Recent studies of the COVID-19 pandemic suggested that some workers experienced better worklife integration and balance when working remotely (37,38). On the contrary, other workers faced increased work-life conflict due to the difficulty in distinguishing between work and life during WFH (39,40), including during the COVID-19 pandemic (41,42).…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%